1999
DOI: 10.1099/13500872-145-7-1721
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of trichloroethene by a linear-plasmid-encoded alkene monooxygenase in Rhodococcus corallinus (Nocardia corallina) B-276

Abstract: Rhodococcus corallinus (formerly Nocardia corallina) 6-276, isolated with propene as sole carbon and energy source, is able to oxidize trichloroethene (TCE). Glucose-or propene-grown R. corallinus B-276 cells exhibited no difference in TCE degradation efficiency. TCE degradation was found to be growth-phase-dependent and maximum rates were monitored with stationaryphase cells. K,,, and V,,, values for TCE degradation of R. corallinus 6-276 grown in nutrient broth medium in the presence of glucose were 187 pM a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
0
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(52 citation statements)
references
References 20 publications
(15 reference statements)
1
50
0
1
Order By: Relevance
“…In addition to unique biochemical reactions, the propene assimilation pathway is also distinguished by unusual genetic elements. In both strains Py2 and B-276, the propene monooxygenase genes are carried on linear megaplasmids, and in strain Py2, the epoxide carboxylase system and CoM biosynthesis genes are also plasmid borne (18,26).As part of the study that yielded strain JS60, we isolated many other mycobacteria that grew on VC (5). It is not known whether these isolates or similar Mycobacterium strains isolated on ethene (6, 7) possess EaCoMT enzymes.…”
mentioning
confidence: 99%
“…In addition to unique biochemical reactions, the propene assimilation pathway is also distinguished by unusual genetic elements. In both strains Py2 and B-276, the propene monooxygenase genes are carried on linear megaplasmids, and in strain Py2, the epoxide carboxylase system and CoM biosynthesis genes are also plasmid borne (18,26).As part of the study that yielded strain JS60, we isolated many other mycobacteria that grew on VC (5). It is not known whether these isolates or similar Mycobacterium strains isolated on ethene (6, 7) possess EaCoMT enzymes.…”
mentioning
confidence: 99%
“…Rhodococcus corallinus B-276 was even found to harbour four linear plasmids, pNC10 (70 kb), pNC20 (85 kb), pNC30 (185 kb) and pNC40 (235 kb). The gene for an alkene monooxygenase, which allows this organism to grow on propene and to co-oxidize trichloroethene, was shown to be located on pNC30 (Saeki et al, 1999). In contrast, only single linear plasmids, pBD2 (210 kb) and pTA421 (500 kb), were detected in the isopropylbenzene-degrading strain R. erythropolis BD2 (Kesseler et al, 1996;Stecker et al, 2003) and the (chloro)biphenyl degrader R. erythropolis TA421 (Kosono et al, 1997), respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Plasmids of rhodococci, which, like their Streptomyces counterparts often possess linear topology, frequently encode catabolic genes, enabling their hosts either to grow with unusual carbon and energy sources such as CO 2 / hydrogen (Kalkus et al, 1990), (chloro)biphenyl (Kosono et al, 1997;Masai et al, 1997), and isopropylbenzene (Dabrock et al, 1994;Stecker et al, 2003) or to just convert such compounds as was shown for trichloroethene (Dabrock et al, 1994;Saeki et al, 1999). In addition, linear plasmids of rhodococci were shown to harbour genes for resistance to thallium (Kalkus et al, 1990) and arsenic (Dabrock et al, 1994;Stecker et al, 2003), as well as genes for phytopathogenicity (Maes et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the broad substrate range [148] allows them to oxidize a variety of halogenated-alkanes, alkenes and aromatics with favourable kinetic parameters [13] and (in some cases) stereo-selectivity [149]. All SDIMO groups so far examined include enzymes capable of co-metabolically oxidizing halogenated pollutants such as trichloroethene (TCE) and vinyl chloride (VC) [150][151][152][153]. Some members showed also the ability to co-metabolize methyl tert-butyl ether (MTBE) [67].…”
Section: Significance Of Sdimo Hydroxylases In Bioremediationmentioning
confidence: 99%